O diálogo como metodologia filosófica para o ensino de filosofia - Sousa, Francisca Evanice Mourão Lima de (2024)
For centuries, philosophy has intrigued and challenged humanity. Generally, it can be defined as the relentless pursuit of knowledge and understanding of the world and ourselves. However, as a challenging discipline, the practice of philosophizing has not always been smooth. The teaching of philosophy in Brazil has a history marked by challenges, as for a long time, philosophy was excluded from the school curriculum, being seen as an inaccessible or unnecessary subject. Nonetheless, the teaching of philosophy still faces obstacles today, especially with the changes proposed by the implementation of the New High School in Brazil. Among the new changes, the educational reform proposes curriculum flexibility, where philosophy is no longer a mandatory subject, even though philosophy inherently aims to teach everything that is targeted by the competencies proposed by the National Common Curricular Base (BNCC). Therefore, the objective of this work is to propose a discussion about the development and application of a dialogical philosophical methodology for the teaching of philosophy. To this end, it is necessary to revisit the roots of philosophical thought and understand the importance of Socrates and Socratic dialectics for the history of philosophy and, consequently, for the teaching of philosophy, in order to enable the application of the Socratic methodology in the contemporary classroom. Known for his philosophical method based on maieutics, Socrates sought knowledge through dialectics. The essence of the Socratic method lies in the idea that knowledge cannot be directly transmitted from a teacher, as a facilitator, to a student, as if the student were merely a repository of information. Socrates believed that every human being possessed latent knowledge within themselves, and his role as a facilitator of knowledge was to stimulate the student to bring this knowledge to light, that is, to give birth to knowledge. Hence the name maieutics. Thus, viewing education as a dialogical process, in which educator and student engage in a horizontal relationship of knowledge and experience exchange, highlights the emancipatory character of education and, in this case, the teaching of philosophy. To achieve the proposed objective of this work, Philosophical Dialogue Workshops were developed, targeting 32 students regularly enrolled in the 3rd year of high school. The methodology was applied during weekly philosophy classes, from September 1 to October 6, 2023, totaling 6 classes dedicated to the workshop's execution. The classes were divided between the presentation of the content to be discussed, the screening of the film that fostered the discussion moment, the dialogue moment, and, finally, the students' evaluation of the methodology. The responses gathered from the evaluation questionnaire reveal the effectiveness of the dialogical methodology as a teaching method. What had already been revealed and tested by Socrates in antiquity proves to be current and relevant as it can be applied in contemporary times.